A pre-oxidized filament for in-situ porosified flow battery thin electrode and a preparation method thereof

CN123005535APending Publication Date: 2026-10-30ZHEJIANG BAOWAN CARBON FIBER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610905378.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-23
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

此类后置造孔手段不仅增加工序、提升生产成本与能耗,还极易破坏纤维本体骨架结构,造成力学强度大幅衰减、孔道大小杂乱无序、盲孔闭口占比高,且活化刻蚀易产生残碳、杂质残留,严重影响超薄碳毡电极的导电稳定性与电解液浸润传质效果

Benefits of technology

(1)本发明采用的脂肪族聚碳酸酯低聚物致孔剂,通过分子量调节器精准控制分子量800-2000,与纺丝体系相容性优异、不水溶、耐高温全流程不流失。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123005535A_ABST
    Figure CN123005535A_ABST
Patent Text Reader

Abstract

The application discloses in-situ pore-forming pre-oxidized wire for thin electrode of liquid flow battery and a preparation method thereof, and belongs to the technical field of functional pre-oxidized wire preparation.The PAN / strong-polarity solvent spinning stock solution is prepared by one-step solution polymerization of acrylonitrile, and aliphatic polycarbonate oligomer is added as a pore-forming agent; the pore-forming agent is prepared by alternating copolymerization of alkylene oxide and carbon dioxide as comonomers, dihydric alcohol as a molecular weight regulator, and double metal cyanide complex as a catalyst, has a number average molecular weight of 800-2000, and is insoluble in water; the original wire is subjected to three-stage gradient pre-oxidation in an air atmosphere; the pore-forming agent is subjected to zipper-like thermal degradation at a high-temperature stage of 240 DEG C or above, is completely decomposed into gaseous small molecules, and in-situ forms 5-20 nm uniform and through nanometer pore channels in the fiber.The pre-oxidized wire prepared by the application has high specific surface area, good mechanical properties and few structural defects, and can be used as a precursor raw material of 0.5-1.5 mm liquid flow battery ultrathin carbon felt electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of functionalized pre-oxidized wire and flow battery electrode preparation technology, specifically to a pre-oxidized wire for in-situ porous flow battery thin electrode and its preparation method. Background Technology

[0002] In the field of flow battery energy storage, the next-generation 0.5-1.5mm ultrathin carbon felt electrode is a core material for improving battery power density, reducing polarization resistance, and enhancing electrolyte mass transfer efficiency. Its performance is highly dependent on the specific surface area, internal nano-interconnected pore structure, fiber mechanical integrity, and dimensional thermal stability of the precursor PAN pre-oxidized filament.

[0003] Currently, the industry generally lacks precise and controllable in-situ pore-forming technology for conventional PAN pre-oxidized fibers, and mostly relies on post-processing methods such as high-temperature steam activation and acid-base chemical etching to create pores. Such post-processing methods not only increase the number of steps, production costs, and energy consumption, but also easily damage the fiber's skeletal structure, resulting in a significant decrease in mechanical strength, disordered pore sizes, and a high proportion of blind and closed pores. Furthermore, activation etching easily produces residual carbon and impurities, which seriously affect the conductivity stability of the ultrathin carbon felt electrode and the electrolyte wetting and mass transfer effect.

[0004] Existing technologies have also attempted to add conventional inorganic salts and polymer particles as pore-forming agents to spinning solutions, but there are obvious technical shortcomings: conventional pore-forming agents have poor compatibility with PAN matrix and highly polar spinning solvents, making it impossible to achieve molecular-level dispersion and easily agglomerating to form large pore defects; moreover, most pore-forming agents have insufficient temperature resistance, and are easily dissolved and lost, or decomposed and coked prematurely during gradient water washing, high-temperature drawing and heat setting of the yarn. This not only makes it impossible to accurately control the narrow distribution of 5-20nm nanopores, but also introduces internal defects, significantly reducing the mechanical and operational stability of pre-oxidized yarn.

[0005] More importantly, existing publicly available technologies lack proprietary molecular structure design and precise molecular weight control methods, and are merely simple replacements of conventional materials. They have weak technological innovation, low patent barriers, and are easily circumvented by competitors through parameter fine-tuning. At the same time, they cannot be adapted to the industrial production system of acrylonitrile one-step solution polymerization to directly produce the raw material. The process adaptability is poor, and the pore-forming and spinning processes cannot be deeply coupled, making it difficult to meet the stringent requirements of high-end flow battery ultrathin electrodes for high specific surface area, highly regular pores, high strength, and low shrinkage of the precursor pre-oxidized filament.

[0006] To address the multiple technical shortcomings of existing technologies, such as post-pore formation damaging fibers, poor compatibility of conventional pore-forming agents leading to easy loss and coking, uncontrollable pore size, lack of a dedicated synthesis and control system, insufficient inventiveness and protection barriers, and difficulty in matching one-step industrial production, this invention proposes a pre-oxidized fiber for thin electrodes of in-situ porous flow batteries and its preparation method. Summary of the Invention

[0007] The purpose of this invention is to overcome the shortcomings of the prior art and provide a PAN-based pre-oxidized filament with in-situ pore formation, high specific surface area, high strength, and suitability for thin electrodes in flow batteries, as well as its preparation method. In-situ nanopore formation is achieved through a one-step polymerization solution, a dedicated pore-forming agent, and a three-stage gradient pre-oxidation process. No subsequent activation or etching is required to obtain a pre-oxidized filament with uniform and interconnected pores, high specific surface area, excellent mechanical properties, and stable dimensions. It is specifically designed for 0.5-1.5mm ultrathin carbon felt electrodes in flow batteries.

[0008] To achieve the above objectives, the present invention adopts the following technical solution: a method for preparing pre-oxidized wire for thin electrodes of flow batteries with in-situ pore formation, comprising the following steps: (1) PAN / strong polar solvent spinning solution was directly prepared by solution polymerization of acrylonitrile and comonomer in one step; (2) Add a porogen at a mass of 0.1-1.0 wt% of PAN to the spinning solution; the porogen is an aliphatic polycarbonate oligomer with a number average molecular weight of 800-2000; (3) The spinning solution is wet-spun to obtain PAN precursor fibers; (4) The PAN precursor fiber is placed in an air atmosphere for gradient pre-oxidation; the gradient pre-oxidation includes three stages of constant temperature in sequence; the temperature of the first stage of constant temperature is 220℃-240℃, the temperature of the second stage of constant temperature is 240℃-250℃, the temperature of the third stage of constant temperature is 265℃-275℃, and the total pre-oxidation time is 30-60min. (5) The pore-forming agent undergoes unzipping thermal degradation in the second and third isothermal stages, completely decomposing into gaseous small molecules, forming in-situ through-hole nanopores with a pore size of 5-20 nm inside the fiber.

[0009] Further, the synthesis method of the pore-forming agent is as follows: using aliphatic epoxy alkane and carbon dioxide as comonomers, diol as molecular weight regulator, and bimetallic cyanide complex as catalyst; carrying out alternating copolymerization reaction at 80-100℃ and 0.5-1.0MPa for 3-5 hours; after the reaction, removing unreacted monomers by vacuum distillation to obtain aliphatic polycarbonate oligomers with a number average molecular weight of 800-2000; wherein the aliphatic epoxy alkane is selected from one or two of propylene oxide and butane oxide, and the diol is at least one of ethylene glycol, 1,3-propanediol, and 1,4-butanediol.

[0010] Preferably, the porogen is selected from one of polypropylene carbonate oligomers, polybutylene carbonate oligomers, or copolymers thereof; the strongly polar solvent is dimethyl sulfoxide (DMSO), dimethylformamide (DMF), or dimethylacetamide (DMAc); the porogen is insoluble in water, and the peak value of the thermal weight loss rate in the temperature range of 230-270°C is not less than 80% / min.

[0011] Preferably, the in-situ formed nanopores have a concentrated pore size distribution of 8-15 nm, and the channels have a three-dimensional through-structure, without collapse, stress concentration, or solid residue coking.

[0012] The porogen described in this invention is an aliphatic polycarbonate oligomer containing a large number of carbonate bonds (-OC(O)-O-) in its molecular chain. Under high temperature conditions (especially above 240°C), the carbonate bonds undergo "zipper-like" thermal degradation, that is, they break sequentially from the ends of the molecular chain, releasing cyclic carbonate monomers or gaseous small molecules such as CO2. Because this invention precisely controls the molecular weight of the porogen to 800-2000, its molecular chain is relatively short and its terminal group density is high. Combined with the aerobic environment of pre-oxidation, rapid, complete, and residue-free thermal degradation can be achieved in the second and third temperature ranges of pre-oxidation, leaving no carbonized residue or stress concentration points inside the fiber. The pore size range of the in-situ nanopores can be synergistically controlled by the molecular weight of the porogen, the amount of porogen added, the pre-oxidation temperature and time, and the draw ratio, achieving precise controllability of the pore size within the range of 5-20 nm, with a concentrated distribution in the 8-15 nm range.

[0013] Furthermore, the obtained pre-oxidized filament has a specific surface area of ​​4.0-7.0 m² / g, a tensile strength of >2.5 cN / dtex, an oxygen index of >42%, and a thermal shrinkage rate of ≤2.0%.

[0014] Further, the wet spinning process described in step (3) involves sequentially undergoing coagulation bath molding, gradient water washing, hot water stretching, oiling, drying and densification, steam stretching, and relaxation heat setting to prepare PAN precursor yarn.

[0015] The present invention also provides a pre-oxidized filament for in-situ porous flow battery thin electrode obtained by the above preparation method, which contains uniform through nanopores of 5-20 nm inside, and the pre-oxidized filament is used as a precursor raw material for preparing 0.5-1.5 mm flow battery carbon felt electrode.

[0016] Compared with the prior art, the present invention has the following advantages: (1) The aliphatic polycarbonate oligomer pore maker used in this invention has a molecular weight of 800-2000 that is precisely controlled by a molecular weight regulator. It has excellent compatibility with the spinning system, is water-insoluble, and is heat-resistant without loss throughout the entire process.

[0017] (2) The three-stage gradient pre-oxidation is used to achieve in-situ unzipping thermal degradation of the pore-forming agent, which is completely decomposed without residue and forms uniform through-holes of 5-20nm in situ. No activation or etching post-treatment is required, and the fiber structure is not damaged.

[0018] (3) The pre-oxidized filament has both high specific surface area and excellent mechanical properties. The specific surface area is 4.0-7.0m² / g, the breaking strength is >2.5cN / dtex, the oxygen index is high and the thermal shrinkage rate is low, which is perfectly compatible with the needle punching of 0.5-1.5mm ultra-thin carbon felt electrode.

[0019] (4) The entire process from spinning solution to pre-oxidation is coupled and controlled, the pore structure is controllable, with fewer defects and high uniformity, which significantly improves the wettability and electrochemical activity of the electrolyte in the flow battery electrode. The process is stable and easy to industrialize. Attached Figure Description

[0020] Figure 1 This is a flowchart of the preparation process of the present invention. Detailed Implementation

[0021] The following is in conjunction with the appendix Figure 1 The present invention provides a detailed description of the specific embodiments of a pre-oxidized wire for an in-situ porous flow battery thin electrode and its preparation method. Example

[0022] A method for preparing a pre-oxidized wire for an in-situ porous flow battery thin electrode includes the following steps: (1) Synthesis of pore-forming agent: propylene oxide and carbon dioxide were used as comonomers, 1,3-propanediol was used as molecular weight regulator, and bimetallic cyanide complex was used as catalyst; the reaction temperature was controlled at 90℃ and the reaction pressure at 0.8MPa, and the copolymerization reaction was carried out alternately for 4h; after the reaction was completed, the unreacted monomers were removed by vacuum distillation to obtain polypropylene carbonate oligomer with a number average molecular weight of 1500.

[0023] (2) Preparation of spinning solution: PAN / DMSO spinning solution was directly prepared by solution polymerization of acrylonitrile and comonomer in one step; 0.5 wt% of the above-mentioned self-made pore-forming agent was added to the spinning solution and stirred evenly.

[0024] (3) Preparation of PAN precursor yarn: The spinning solution is wet spun and then successively subjected to coagulation bath molding, gradient water washing, hot water stretching, oiling, drying and densification, steam stretching, and relaxation heat setting to obtain PAN precursor yarn.

[0025] (4) Three-stage gradient pre-oxidation: the first stage is kept at 230℃ for 15 min, the second stage is kept at 245℃ for 20 min, and the third stage is kept at 270℃ for 15 min, for a total time of 50 min; the pore-forming agent undergoes unzipping thermal degradation in the second and third stage isothermal stages, completely decomposes into gaseous small molecules, and forms in-situ through-holes of 5-18 nm and concentrated 8-12 nm.

[0026] The properties of the obtained pre-oxidized fiber are: specific surface area 5.5 m² / g, tensile strength 2.8 cN / dtex, oxygen index 44%, thermal shrinkage rate 1.8%, uniform and continuous pores, and no residue or coking. Example

[0027] A method for preparing a pre-oxidized wire for an in-situ porous flow battery thin electrode includes the following steps: (1) Synthesis of pore-forming agent: Epoxy butane and carbon dioxide were used as comonomers, 1,4-butanediol was used as molecular weight regulator, and bimetallic cyanide complex was used as catalyst; the reaction temperature was controlled at 85℃ and the reaction pressure at 0.6MPa, and the copolymerization reaction was carried out alternately for 3.5h; after the reaction was completed, the unreacted monomers were removed by vacuum distillation to obtain polybutylene carbonate oligomer with a number average molecular weight of 1200.

[0028] (2) Preparation of spinning solution: PAN / DMSO spinning solution was directly prepared by solution polymerization of acrylonitrile and comonomer in one step; the above-mentioned self-made pore-forming agent at 0.3 wt% of PAN mass was added to the spinning solution and stirred evenly.

[0029] (3) Preparation of PAN precursor yarn: The spinning solution is wet spun and then successively subjected to coagulation bath molding, gradient water washing, hot water stretching, oiling, drying and densification, steam stretching, and relaxation heat setting to obtain PAN precursor yarn.

[0030] (4) Three-stage gradient pre-oxidation: the first stage is kept at 225℃ for 12 min, the second stage is kept at 240℃ for 18 min, and the third stage is kept at 265℃ for 15 min, for a total time of 45 min; the pore-forming agent undergoes unzipping thermal degradation in the second and third stage isothermal stages, completely decomposes into gaseous small molecules, and forms 5-15 nm and concentrated 6-10 nm through nanopores in situ.

[0031] The properties of the obtained pre-oxidized fiber are: specific surface area 4.8 m² / g, tensile strength 2.7 cN / dtex, oxygen index 42.5%, thermal shrinkage rate 1.9%, uniform and continuous pores, and no residue or coking. Example

[0032] A method for preparing a pre-oxidized wire for an in-situ porous flow battery thin electrode includes the following steps: (1) Synthesis of pore-forming agent: propylene oxide, butane oxide and carbon dioxide were used as comonomers, ethylene glycol was used as molecular weight regulator and bimetallic cyanide complex was used as catalyst; the reaction temperature was controlled at 80℃ and the reaction pressure at 0.9MPa, and the copolymerization reaction was carried out alternately for 5h; after the reaction was completed, the unreacted monomers were removed by vacuum distillation to obtain a copolymeric aliphatic polycarbonate oligomer with a number average molecular weight of 1800.

[0033] (2) Preparation of spinning solution: PAN / DMSO spinning solution was directly prepared by solution polymerization of acrylonitrile and comonomer in one step; 0.8 wt% of the above-mentioned self-made pore-forming agent was added to the spinning solution and stirred evenly.

[0034] (3) Preparation of PAN precursor yarn: The spinning solution is wet spun and then successively subjected to coagulation bath molding, gradient water washing, hot water stretching, oiling, drying and densification, steam stretching, and relaxation heat setting to obtain PAN precursor yarn.

[0035] (4) Three-stage gradient pre-oxidation: the first stage is kept at 240℃ for 10 min, the second stage is kept at 250℃ for 15 min, and the third stage is kept at 275℃ for 15 min, for a total time of 40 min; the pore-forming agent undergoes unzipping thermal degradation in the second and third stage isothermal stages, completely decomposing into gaseous small molecules, forming in-situ through-holes of 8-20 nm and concentrated 10-15 nm.

[0036] The properties of the obtained pre-oxidized fiber are: specific surface area 6.5 m² / g, tensile strength 2.6 cN / dtex, oxygen index 45%, thermal shrinkage rate 1.7%, uniform and continuous pores, and no residue or coking. Example

[0037] A method for preparing a pre-oxidized wire for an in-situ porous flow battery thin electrode includes the following steps: (1) Synthesis of pore-forming agent: propylene oxide and carbon dioxide were used as comonomers, ethylene glycol was used as molecular weight regulator, and bimetallic cyanide complex was used as catalyst; the reaction temperature was controlled at 90℃ and the reaction pressure at 0.7MPa, and the copolymerization reaction was carried out alternately for 3h; after the reaction was completed, the unreacted monomers were removed by vacuum distillation to obtain polypropylene carbonate oligomer with a number average molecular weight of 1000.

[0038] (2) Preparation of spinning solution: PAN / DMSO spinning solution was directly prepared by solution polymerization of acrylonitrile and comonomer in one step; 0.2 wt% of the above-mentioned self-made pore-forming agent was added to the spinning solution and stirred evenly.

[0039] (3) Preparation of PAN precursor yarn: The spinning solution is wet spun and then successively subjected to coagulation bath molding, gradient water washing, hot water stretching, oiling, drying and densification, steam stretching, and relaxation heat setting to obtain PAN precursor yarn.

[0040] (4) Three-stage gradient pre-oxidation: the first stage is kept at 220℃ for 20 min, the second stage is kept at 240℃ for 20 min, and the third stage is kept at 265℃ for 20 min, for a total time of 60 min; the pore-forming agent undergoes unzipping thermal degradation in the second and third stage isothermal stages, completely decomposes into gaseous small molecules, and forms 5-12 nm and concentrated 6-9 nm through nanopores in situ.

[0041] The properties of the obtained pre-oxidized fiber are: specific surface area 4.2 m² / g, tensile strength 2.9 cN / dtex, oxygen index 42%, thermal shrinkage rate 1.9%, uniform and continuous pores, and no residue or coking. Example

[0042] A method for preparing a pre-oxidized wire for an in-situ porous flow battery thin electrode includes the following steps: (1) Synthesis of pore-forming agent: Epoxy butane and carbon dioxide were used as comonomers, 1,3-propanediol was used as molecular weight regulator, and bimetallic cyanide complex was used as catalyst; the reaction temperature was controlled at 85℃ and the reaction pressure at 0.9MPa, and the copolymerization reaction was carried out alternately for 4.5h; after the reaction was completed, the unreacted monomers were removed by vacuum distillation to obtain polypropylene carbonate oligomer with a number average molecular weight of 2000.

[0043] (2) Preparation of spinning solution: PAN / DMSO spinning solution was directly prepared by solution polymerization of acrylonitrile and comonomer in one step; 1.0 wt% of the above-mentioned self-made pore-forming agent was added to the spinning solution and stirred evenly.

[0044] (3) Preparation of PAN precursor yarn: The spinning solution is wet spun and then successively subjected to coagulation bath molding, gradient water washing, hot water stretching, oiling, drying and densification, steam stretching, and relaxation heat setting to obtain PAN precursor yarn.

[0045] (4) Three-stage gradient pre-oxidation: the first stage is kept at 240℃ for 10 min, the second stage is kept at 250℃ for 10 min, and the third stage is kept at 275℃ for 10 min, for a total time of 30 min; the pore-forming agent undergoes unzipping thermal degradation in the second and third stage isothermal stages, completely decomposes into gaseous small molecules, and forms 10-20 nm and concentrated 12-18 nm through nanopores in situ.

[0046] The properties of the obtained pre-oxidized fiber are: specific surface area 6.9 m² / g, tensile strength 2.5 cN / dtex, oxygen index 44%, thermal shrinkage rate 1.6%, uniform and continuous pores, and no residue or coking.

[0047] Comparative Example 1: Compared to Example 1, no pore-forming agent was added, and other process conditions were the same.

[0048] The properties of the obtained pre-oxidized fiber are: specific surface area 1.8 m² / g, breaking strength 2.8 cN / dtex, oxygen index 39%, heat shrinkage rate 2.9%, and the fiber is dense without nanopores.

[0049] Comparative Example 2: Compared with Example 1, commercially available conventional polycarbonate particles (molecular weight 25,000-35,000) were used instead of the pore-forming agent of the present invention, while other process conditions remained the same.

[0050] The properties of the obtained pre-oxidized fiber are: specific surface area 2.3 m² / g, tensile strength 2.1 cN / dtex, oxygen index 39%, heat shrinkage rate 3.2%, uneven pores, agglomerated macropores and residual carbon.

[0051] Conclusion of technical effect comparison: Comparative tests of Comparative Example 1 (without porogen), Comparative Example 2 (with commercially available conventional high molecular weight polycarbonate particles), and Examples 1-5 of the present invention (with aliphatic polycarbonate oligomer porogens of molecular weight 800-2000) yielded the following conclusions: Compared to Comparative Example 1, the PAN pre-oxidized fiber without the added pore-forming agent has a dense fiber structure, low specific surface area, low oxygen index, and high thermal shrinkage rate. Although it has high mechanical strength, the lack of nano-interconnected channels results in poor electrolyte wettability, which cannot meet the requirements for use in ultra-thin flow electrodes. This invention, by introducing a dedicated pore-forming agent, significantly improves the specific surface area and oxygen index of the pre-oxidized fiber, and significantly reduces the thermal shrinkage rate. Simultaneously, the fiber skeleton is not significantly damaged, and the tensile strength remains at a good level, making it suitable for the needle-punching process of ultra-thin electrodes.

[0052] II. Compared to Comparative Example 2, commercially available conventional high molecular weight polycarbonate has poor compatibility with PAN and highly polar spinning solvents, making it difficult to disperse uniformly and easily forming agglomerated macropores within the fiber. Furthermore, this material lacks thermal stability and compatibility, easily decomposing prematurely or incompletely during spinning and pre-oxidation processes, resulting in residual carbon coking. The final product exhibits disordered pores, deteriorated mechanical properties, and poor overall performance. This invention utilizes aliphatic polycarbonate oligomers with a defined molecular weight, exhibiting excellent compatibility with the spinning system and being insoluble in water, preventing loss during wet processes such as washing and drawing. Combined with its high internal thermal weight loss characteristics, it undergoes complete unzipping thermal degradation in the pre-oxidation zone, without the formation of solid residues, ultimately forming uniformly distributed, interconnected nanopores. The product's overall performance is superior to conventional porous systems.

[0053] III. As can be seen from the various embodiments of the present invention, with the increase of the amount of pore-forming agent added, the specific surface area of ​​the pre-oxidized fiber increases, the pore size distribution range widens, the breaking strength decreases slightly but still meets the usage requirements, the oxygen index remains stable at an excellent value, and the thermal shrinkage rate gradually decreases (the internal pores can buffer the thermal deformation of the fiber). The present invention can achieve precise control of the nanopore size by adjusting the molecular weight and amount of pore-forming agent, with a wide adjustable range of processes and good industrial adaptability.

[0054] In summary, this invention successfully achieves the in-situ formation of uniform, interconnected nanopores within PAN pre-oxidized fibers by employing a molecular weight-controllable aliphatic polycarbonate oligomer pore-forming agents and deeply coupling them with a one-step solution polymerization spinning solution for acrylonitrile and a three-stage gradient pre-oxidation process, without requiring any post-treatment activation or etching steps. The resulting pre-oxidized fibers possess high specific surface area, high tensile strength, high oxygen index, and low thermal shrinkage, exhibiting significantly superior overall performance compared to existing technologies. They can serve as a dedicated precursor material for ultra-thin carbon felt electrodes in 0.5-1.5mm flow batteries, providing crucial material support for improving flow battery power density, reducing polarization resistance, and enhancing electrolyte mass transfer efficiency.

[0055] The above description is merely a preferred embodiment of the present invention. The scope of protection of the present invention is not limited to the above embodiments. All technical solutions falling within the scope of the present invention's concept are within the scope of protection of the present invention. It should be noted that for those skilled in the art, any improvements and modifications made without departing from the principles of the present invention should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing pre-oxidized wire for thin electrodes in in-situ porous flow batteries, characterized in that, Includes the following steps: (1) PAN / strong polar solvent spinning solution was directly prepared by solution polymerization of acrylonitrile and comonomer in one step; (2) Add a porogen at a mass of 0.1-1.0 wt% of PAN to the spinning solution; the porogen is an aliphatic polycarbonate oligomer with a number average molecular weight of 800-2000; (3) The spinning solution is wet-spun to obtain PAN precursor fibers; (4) The PAN precursor fiber is placed in an air atmosphere for gradient pre-oxidation; the gradient pre-oxidation includes three stages of constant temperature in sequence; the temperature of the first stage of constant temperature is 220℃-240℃, the temperature of the second stage of constant temperature is 240℃-250℃, the temperature of the third stage of constant temperature is 265℃-275℃, and the total pre-oxidation time is 30-60min. (5) The pore-forming agent undergoes unzipping thermal degradation in the second and third isothermal stages, completely decomposing into gaseous small molecules, forming in-situ through-hole nanopores with a pore size of 5-20 nm inside the fiber.

2. The method for preparing pre-oxidized wire for in-situ porous flow battery thin electrodes according to claim 1, characterized in that, The pore-forming agent is synthesized using the following method: aliphatic epoxy alkane and carbon dioxide are used as comonomers, a diol is used as a molecular weight regulator, and a bimetallic cyanide complex is used as a catalyst; an alternating copolymerization reaction is carried out at 80-100℃ and 0.5-1.0MPa for 3-5 hours; after the reaction, unreacted monomers are removed by vacuum distillation to obtain aliphatic polycarbonate oligomers with a number average molecular weight of 800-2000; the aliphatic epoxy alkane is selected from one or two of propylene oxide and butane oxide, and the diol is at least one of ethylene glycol, 1,3-propanediol, and 1,4-butanediol.

3. The method for preparing pre-oxidized wire for in-situ porous flow battery thin electrodes according to claim 1, characterized in that, The porogen is selected from one of polypropylene carbonate oligomers, polybutylene carbonate oligomers, or copolymers thereof; the strongly polar solvent is dimethyl sulfoxide, dimethylformamide, or dimethylacetamide; the porogen is insoluble in water.

4. The method for preparing pre-oxidized wire for in-situ porous flow battery thin electrodes according to claim 1, characterized in that, The peak thermal weight loss rate of the porogen in the temperature range of 230-270℃ is not less than 80% / min.

5. The method for preparing pre-oxidized wire for in-situ porous flow battery thin electrodes according to claim 1, characterized in that, The pore size of the in-situ formed nanopores is concentrated in the range of 8-15 nm.

6. The method for preparing pre-oxidized wire for in-situ porous flow battery thin electrodes according to claim 1, characterized in that, The obtained pre-oxidized fiber has a specific surface area of ​​4.0-7.0 m² / g, a tensile strength of >2.5 cN / dtex, an oxygen index of >42%, and a thermal shrinkage rate of ≤2.0%.

7. The method for preparing pre-oxidized wire for in-situ porous flow battery thin electrodes according to claim 1, characterized in that, In step (3), the wet spinning process is carried out in sequence through coagulation bath molding, gradient water washing, hot water stretching, oiling, drying and densification, steam stretching, and relaxation heat setting to prepare PAN precursor yarn.

8. A pre-oxidized wire for a thin electrode in an in-situ porous flow battery, characterized in that, Prepared by the method described in any one of claims 1-7, it contains through-nanopores of 5-20 nm inside.

9. The application of the pre-oxidized filament according to claim 8 in the preparation of 0.5-1.5 mm flow battery carbon felt electrode.